Soft Exchange Rate Bands and Speculative Attacks : Theory, and Evidence from the ERM since August 1993 - Bartolini, Leonardo (IMF Working Papers; Working Paper ;, 1998)
We present a model of a 'soft' exchange rate target zone and interpret it as a stylized description of the post-August 1993 ERM. Our central bank targets a moving average of the current and past exchange rates, rather than the exchange rate's current level, thus allowing the rate to move within wide margins in the short run, but within narrow margins in the long run. For realistic parameters, soft target zones are significantly less vulnerable to speculative attacks than 'hard' target zones. These predictions are consistent with the ERM's experience and the abatement of speculative pressure in European markets since the bands' widening in 1993.